Analisis Mikrobiologis Jus Buah Pinang (Areca Catechu L.): Pendekatan Eksperimen Mikrobiologis - Nindy Adisha Puti Hanumsari; Ardi Mustakim (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The betel nut (Areca catechu) is a tropical plant that thrives in Southeast Asia, including Indonesia. This plant has long been known in traditional medicine and local culture for its content of various beneficial active compounds. One form of its utilization that has rarely been scientifically studied is fresh betel nut juice. Therefore, this study aims to conduct a preliminary assessment of the characteristics of fresh betel nut juice, particularly from a physical, chemical, and microbiological perspective. The juice production process is carried out simply by squeezing fresh betel nuts without the addition of chemicals or heating. Based on initial observations, the betel nut juice exhibits a distinctive reddish-brown color and a sharp, pungent aroma. This color and aroma likely originate from the phenolic and alkaloid compounds naturally present in the betel nut. pH measurements indicate that the juice has a fairly high acidity level, which can affect the stability of microorganisms within it. Qualitative tests of the chemical composition of the betel nut juice indicate the presence of bioactive compounds, particularly tannins and alkaloids. Tannins are known to have antimicrobial activity, while alkaloids act as physiologically active compounds that can affect the nervous system. However, the presence of these compounds does not completely inhibit the growth of microorganisms. Through simple isolation of microorganisms from the fresh juice, bacteria from the genus Lactobacillus spp., which are typically associated with natural fermentation processes, were found. The presence of these bacteria indicates that fresh areca nut juice can be a potential growth medium for certain microorganisms, particularly lactic acid bacteria. This finding opens up opportunities for further research into the use of areca nut juice as a natural fermentation agent that may have functional and probiotic value.